2019
DOI: 10.1051/0004-6361/201834300
|View full text |Cite
|
Sign up to set email alerts
|

Histogram of oriented gradients: a technique for the study of molecular cloud formation

Abstract: We introduce the histogram of oriented gradients (HOG), a tool developed for machine vision that we propose as a new metric for the systematic characterization of spectral line observations of atomic and molecular gas and the study of molecular cloud formation models. In essence, the HOG technique takes as input extended spectral-line observations from two tracers and provides an estimate of their spatial correlation across velocity channels. We characterize HOG using synthetic observations of Hi and 13 CO (J … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 93 publications
0
39
1
Order By: Relevance
“…Second, although there is a morphological correlation of the HI and the 13 CO, as quantified in Soler et al (2019), the filamentary structure in the HI emission is not necessarily related to that of the 13 CO. In general, the much larger filling factor of the HI makes it unlikely that most of its structure is related to that of the less-filling molecular gas.…”
Section: Relation To the Structure Of The Molecular Gasmentioning
confidence: 99%
“…Second, although there is a morphological correlation of the HI and the 13 CO, as quantified in Soler et al (2019), the filamentary structure in the HI emission is not necessarily related to that of the 13 CO. In general, the much larger filling factor of the HI makes it unlikely that most of its structure is related to that of the less-filling molecular gas.…”
Section: Relation To the Structure Of The Molecular Gasmentioning
confidence: 99%
“…In Appendix B we briefly outline the basic principles involved in this method. A comprehensive description is given by Soler et al (2019).…”
Section: Spatial Correlation Between Atomic and Molecular Gasmentioning
confidence: 99%
“…The Histogram of Oriented Gradients (HOG; Soler et al 2019) is based on the assumption that the appearance and shape of an object can be characterized by the representation of its local intensity gradients. One simple application is deriving the spatial correlation between two images.…”
Section: Appendix A: H I Self-absorption Uncertainties Appendix B: Himentioning
confidence: 99%
“…They therefore erroneously assumed that in thin velocity channels all intensity fluctuations are due to density enhancements. Soler et al (2019) and used different approaches in the analysis of intensity distributions in thin velocity channels 6 . The former does not use the procedure of sub-block averaging, which is disadvantageous and prevents Soler et al (2019) from reliably tracing magnetic field direction as it is demonstrated in ; Hu et al (2019a,b); González-Casanova & Lazarian (2019) To compare IGT and HRO, we follow the recipe used in Soler et al (2013), which calculates θ using a combination of the scalar and vector product of vectors:…”
Section: Histogram Of the Relative Orientation 71 Differences And Cmentioning
confidence: 99%
“…VGT, in contrast, explores the pointwise statistics of the magnetic field and does not require any outside measurements. In addition, some of VGT ideas and approaches were successfully borrowed and implemented within HRO as it was evolving (see Soler et al 2019).…”
Section: Introductionmentioning
confidence: 99%